Studi Empiris Dampak Implementasi Tqm Dan Adopsi Tik Terhadap Kinerja Operasi Pada Pdam Di Jawa Barat - Supriyadi Supriyadi (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2014)
In an effort to make improvements, Perpamsi has introduced Total Quality Management (TQM) to the Regional Water Company (PDAM) in West Java. In addition, improvement efforts are also made through the use of technological developments by adopting Information and Communication Technology (ICT) to support the company's operations. This study aims to gain an overview of TQM implementation and adoption of ICT at PDAM in West Java as well as analyze the impact on operating performance. The objects of this analysis are 22 companies of PDAM. Data were collected by questionnaire and the respondent is a manager-level employees. Data were analyzed using multiple regression. The results showed that the TQM implementation and adoption of ICT at PDAM in West Java are not maximized yet. Partially, TQM implementation and adoption of ICT provide a significant positive impact on the improvement of operating performance